2017
DOI: 10.3389/fpubh.2017.00311
|View full text |Cite
|
Sign up to set email alerts
|

Association between Depression and Factors Affecting Career Choice among Jordanian Nursing Students

Abstract: BackgroundAlthough stress reaction is high among nursing staff and nursing students in the Middle East and its effect on life is known, there are scant studies reporting on these clinical and social features. In addition, there are no studies reporting on factors that influence career choice among this group.AimThis study aimed to investigate factors that influence career choice among nursing students and their possible association with depressive symptoms.MethodParticipants were 150 (84.7% response rate) nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
2
17
2
2
Order By: Relevance
“…Our study discovered that both factors, selfesteem and interest in nursing, were significantly associated with depression. Our study found that self-esteem had a significant negative correlation with depression, and this result is found in other findings of previous studies (Ross et al, 2009;Yousef et al, 2017;Orth and Robins, 2013), in which higher depression scores were associated with lower selfesteem. This study has also revealed that the best significant predictor to decrease students' depression level is self-esteem.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study discovered that both factors, selfesteem and interest in nursing, were significantly associated with depression. Our study found that self-esteem had a significant negative correlation with depression, and this result is found in other findings of previous studies (Ross et al, 2009;Yousef et al, 2017;Orth and Robins, 2013), in which higher depression scores were associated with lower selfesteem. This study has also revealed that the best significant predictor to decrease students' depression level is self-esteem.…”
Section: Discussionsupporting
confidence: 91%
“…Early research has revealed that the principal causes of stress among nursing students included: adapting to a tedious theory program, complying with overwhelming number of assignments and workload, and acclimating to the rigors of the clinical exposure (Aiken et al, 2011;Alsaqri, 2017). Prolonged subjection to stressors may result in anxiety and discontentedness and even depression (Yousef et al, 2017). Depression is considered as the disease of the twenty-first century (WHO, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…과정에 나타나는 진로에 대한 확고한 정도를 의미하며 [6] [15,16], 진로결정 수준의 영향요인으 로 우울, 주관적 건강 등의 심리적 요인 [17,18], 진로결정 자기효능감 [1,19], 진로의사결정 유형 [11] 및 진로탐색행동 [13]…”
unclassified
“…Similar observation was also made by Nagendra k et al (2012) 12 . On other hand studies by Yousef et al (2017) 13 , Singh A et al (2010) 14 reported a higher prevalence of depression among males than female. kumar GS et al (2012) 8 , Joseph et al (2011) 15 , observed higher prevalence of depression in female than males but statistically not significant.…”
Section: Discussionmentioning
confidence: 90%